2020
DOI: 10.1097/hjh.0000000000002370
|View full text |Cite
|
Sign up to set email alerts
|

May measurement month 2017: Latin America

Abstract: Objectives: To raise awareness of blood pressure, measured by number of countries involved, number of people screened, and number of people who have untreated or inadequately treated hypertension. Methods: An opportunistic cross-sectional survey of volunteers aged at least 18 years was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard May measurement month protocol. Eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…Fewer than half receiving the various classes of antihypertensive medication had their BP under control. Barbosa et al 9 had reported 40.4% hypertension in Latin America in the MMM 2017 campaign, while the MMM 2017 Jamaican data reported 47.3%. 4 Rates in Jamaica were higher than the international rates of 34.9% in 2017, 33.4% in 2018, and 33.4% in 2019.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fewer than half receiving the various classes of antihypertensive medication had their BP under control. Barbosa et al 9 had reported 40.4% hypertension in Latin America in the MMM 2017 campaign, while the MMM 2017 Jamaican data reported 47.3%. 4 Rates in Jamaica were higher than the international rates of 34.9% in 2017, 33.4% in 2018, and 33.4% in 2019.…”
Section: Discussionmentioning
confidence: 95%
“…Demographic data were collected for each volunteer using a standardized survey Excel spreadsheet designed by the International Society of Hypertension (ISH). 8 , 9 Variables obtained included age, sex, ethnicity, medications, previous diagnosis of hypertension, diabetes, myocardial infarction (MI), or stroke. Data were analysed centrally by the MMM project team and multiple imputations performed to impute the mean of readings two and three where all three readings were not available using global level data and using the approach described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Another study followed Cd measurements in the blood from study participants from every parish in Jamaica and their correlation with elevated blood pressure. 1 The study investigated the association between blood Cd levels with blood pressure levels and the prevalence of hypertension in a representative sample of Jamaican adults living in parishes across levels of Cd in local soil. Data were collected through structured questionnaires, blood pressure readings and analyzed using spectrometric techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Trends in non-communicable diseases (NCD) such as chronic kidney disease (CKD), hypertension and diabetes mellitus in the Caribbean mirror the global NCD pandemic which predicts an exponential increase in incidence and prevalence over the next decade. 1 , 2 These NCD, as well as others, are responsible for almost 70% of global deaths. 3 At the 13th Annual Conference on Nephrology and Hypertension held in Kingston, Jamaica on January 2021, it was reported that there were currently more than 2700 CKD patients in Jamaica.…”
Section: Introductionmentioning
confidence: 99%
“…17 Lack of identification of people whose blood pressure is high or normal only when outside the clinic setting (e.g., white coat hypertension and masked hypertension)** Where feasible and affordable, encourage the use of out-of-clinical office BP readings (i.e., community, home or ambulatory) to confirm the diagnosis and monitor BP control. 45 , 46 Ambulatory blood pressure devices are designed to take many blood pressure readings at regular intervals in people who follow their usual daily routines. Home blood pressures are those taken in a home environment, while community blood pressures refer to readings taken outside the home and clinical office (e.g., a pharmacy).…”
Section: Beyond the Who Hypertension Guideline A Strategic Approach F...mentioning
confidence: 99%